2011
DOI: 10.1007/s00300-011-1100-4
|View full text |Cite
|
Sign up to set email alerts
|

Heterotrophic bacterial diversity in aquatic microbial mat communities from Antarctica

Abstract: 25Heterotrophic bacteria isolated from five aquatic microbial mat samples from different locations in 26 continental Antarctica and the Antarctic Peninsula were compared to assess their biodiversity. A total of 27 2225 isolates obtained on different media and at different temperatures were included. After an initial 28 grouping by whole-genome fingerprinting, partial 16S rRNA gene sequence analysis was used for further 29 identification. These results were compared with previously published data obtained with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 69 publications
4
52
0
Order By: Relevance
“…The common Antarctic bacterial phyla such as Actinobacteria, Bacteroidetes, and Proteobacteria, and genera such as Arthrobacter, Flavobacterium, Rhodococcus, Cryobacterium, and Pseudomonas reported by Foong et al (2010), Peeters et al (2012), and Teo and Wong (2014) were also found in Estrellas and CLs. Actinobacteria and Bacteroidetes were the most abundant bacterial families in CL, while Actinobacteria dominates the bacterial community in EL.…”
Section: Types Of Bacteriamentioning
confidence: 96%
“…The common Antarctic bacterial phyla such as Actinobacteria, Bacteroidetes, and Proteobacteria, and genera such as Arthrobacter, Flavobacterium, Rhodococcus, Cryobacterium, and Pseudomonas reported by Foong et al (2010), Peeters et al (2012), and Teo and Wong (2014) were also found in Estrellas and CLs. Actinobacteria and Bacteroidetes were the most abundant bacterial families in CL, while Actinobacteria dominates the bacterial community in EL.…”
Section: Types Of Bacteriamentioning
confidence: 96%
“…There is increasing molecular and classical biogeographic evidence for ancient radiations and vicariance (e.g., Allegrucci et al 2006, Maslen and Convey 2006, Chown and Convey 2007, and/or expansion from refugial centers within the region itself, and survival through (at least) multiple Pleistocene glacial cycles , McGaughran et al 2010, Mortimer et al 2011a). Even apparently highly dispersible groups such as some Antarctic soil microbiota carry a strong signal of long-term geographical isolation, suggesting that local radiation on evolutionary timescales has outweighed the influence of incoming dispersers (De Wever et al 2009, Chong et al 2012, Peeters et al 2012). …”
Section: Spatial Variation At the Largest Extentsmentioning
confidence: 99%
“…The cultured heterotrophic bacterial diversity of these samples was reported earlier [4], [33], [34], [35]. From these, we selected 1,666 high quality sequences for comparison with pyrosequencing.…”
Section: Methodsmentioning
confidence: 99%